Biomaterial Crack Geometry Estimation Using Eddy Current Inverse Approach - Smetana, Milan; Behun, Lukas; Gombarska, Daniela; Janousek, Ladislav (19th International Conference Computational Problems of Electrical Engineering, 2018)
The main subject of this paper is inverse problem approach to non-destructive evaluation of conductive austenitic stainless steel as biomaterials. Eddy current evaluation under harmonic excitation is used. Magneto-resistive effect sensors are there in the role of pick-up elements. Basic cracks geometry is inversely estimated based on computational algorithms. The gained results are presented and discussed in the paper.